Geosocial Networking Dating App Usage and Risky Sexual Behavior in Young Adults Attending a Music Festival: Cross-sectional Questionnaire Study - Garga, Shirali; Thomas, Meryl; Bhatia, Ashneet; Sullivan, Aidan; John-Leader, Franklin; Pit, Sabrina (JMIR Publications, 2021)
BackgroundDespite the prevalent use of geosocial networking dating apps (GNDAs), there is limited research on their impact on sexual health outcomes among young music festivals attendees. ObjectiveThis study aims to explore the use of GNDAs and risky sexual behaviors of young adults attending a music festival. MethodsThe music festival attendees (N=862) completed a cross-sectional questionnaire study encompassing demographics, dating app use, and risky sexual behaviors in the past year. Associations between these variables were estimated using bivariate and multivariate logistic regression analyses. ResultsOf the respondents, 51.9% (448/862) had used GNDAs in the previous year. Compared with people who had 1 partner, people who had 2-5 sexual partners in the previous year had almost 7 times the odds of using dating apps (odds ratio [OR] 6.581, 95% CI 4.643-9.328) and those who had more than 5 partners had 14 times the odds of using dating apps (OR 14.294, 95% CI 8.92-22.906). Condom users were more likely to be app users (P<.001), as were those who relied on emergency Plan B (P=.002), but people using hormonal contraception were less likely to use dating apps (P=.004). After adjusting for sexual orientation and relationship status, those having casual sex had 3.096 (95% CI 2.225-4.307; P<.001) times the odds of using dating apps and those having multiple sexual partners had 3.943 (95% CI 2.782-5.588; P<.001) times the odds of using dating apps. Similarly, after adjusting for sexual orientation, relationship status, and number of sexual partners, people who had no discussions before having sex about sexually transmitted infections (STIs) or boundaries were more likely to use dating apps (OR 1.755, 95% CI 1.232-2.500; P=.002). Those who perceived the risk of having sex without contraception to be very high had 2.486 (95% CI 2.213-5.096; P=.01) times the odds of using dating apps than those who perceived no risk. Compared with those who perceived no risk, people who thought that the risk of having multiple sexual partners was low to high had 1.871 (95% CI 1.024-3.418; P=.04) times the odds of using dating apps. A significant number of app users (389/440, 88.4%) indicated that GNDAs should promote safe sex. ConclusionsThis study identified that festival goers engaging in certain high-risk sexual behaviors, including casual sex, having multiple sexual partners, and having sex without discussion about STI status and boundaries, are more likely to use dating apps. Festival goers who perceived sex without any form of contraception, having sex while drunk, and having multiple sexual partners as risky were more likely to be app users. Policy makers and GNDA developers should acknowledge the vulnerability of their users to adverse sexual health outcomes and use GNDAs as a platform to promote risk-reduction practices.